2008
DOI: 10.1002/acp.1474
|View full text |Cite
|
Sign up to set email alerts
|

Reply scoring and reporting: A response to bond (2008)

Abstract: Bond (2008) objects to the attention given to two of our publications on lie detection accuracy because of what he suggests is incompetence in one case and suppression of data in the other. It is our opinion that his claims are based principally on a tortured re-interpretation of a manuscript we attempted to publish that he has kept in his possession for more than a decade and cites without our permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In order for a judge or an observer to make an accurate assessment of a person’s truthfulness, the individual must demonstrate behaviors relevant to the state or trait of truthfulness or deception (David Funder, personal communication, July 23, 2008). This aspect of the model is particularly germane to the present report in which we argue that the lie or truth being told must be sufficiently important, consequential or motivating to stimulate such behaviors in the target (see also Ekman, O’Sullivan, & Frank, 2008). The second stage of the model is termed availability.…”
Section: Theoretical Assumptionsmentioning
confidence: 73%
See 2 more Smart Citations
“…In order for a judge or an observer to make an accurate assessment of a person’s truthfulness, the individual must demonstrate behaviors relevant to the state or trait of truthfulness or deception (David Funder, personal communication, July 23, 2008). This aspect of the model is particularly germane to the present report in which we argue that the lie or truth being told must be sufficiently important, consequential or motivating to stimulate such behaviors in the target (see also Ekman, O’Sullivan, & Frank, 2008). The second stage of the model is termed availability.…”
Section: Theoretical Assumptionsmentioning
confidence: 73%
“…A designation of a lie scenario as ''high stakes,'' therefore, is meant to convey that for most people involved in it, a moderate to high level of motivation to succeed in lying or telling the truth has been achieved, either because the lie is personally relevant, the rewards are high, or the punishments are significant. We make this assumption for some of the high stakes studies included in this review because we note that only a few of them actually measured whether there were relevant behaviors that discriminated liars from truth tellers (e.g., Ekman, O'Sullivan, & Frank, 2008;Frank & Ekman, 1997;Vrij, 1994).…”
Section: Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Bond (2008) suspected manipulation and believed that Ekman and colleagues avoided reporting the findings that went against their general conclusion. Ekman, O'Sullivan, and Frank (2008) denied manipulation. They reported that after 1997, they tested additional groups of participants but that these new groups did not complete all the lie-detection tests that the earlier groups had completed.…”
Section: Endnotesmentioning
confidence: 99%
“…Needless to say, these claims were greeted with skepticism (see Bond, 2008; Bond & Uysal, 2007; cf. Ekman et al, 2008).…”
Section: Misconception No 4: the Body Never Liesmentioning
confidence: 99%